2021
DOI: 10.1063/5.0034050
|View full text |Cite|
|
Sign up to set email alerts
|

A planar microwave resonator with odd resonance for calibration in permanent moisture sensing applications

Abstract: A cylindrical dual-mode planar microwave ring resonator for a permanent moisture sensor is presented. The ring is design for TMn10 fundamental (odd-mode) resonance, and optimized to sustain stability (suitable for calibration reference against environmental interference) using Ansys high-frequency structure simulator. An even-mode resonance is perturbed by etching a step-impedance stub on the upper 0.5λ ring. The equations for the TMn10 mode resonance and its mode splitting are stated. The equivalent circuits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…For CSRR-based sensors, the ratio C /C that appears in (11) can be evaluated by isolating C and C from (7), however, the resulting expression is not as simple as (12). In this case, it is found that C /C is (13) and the dielectric constant of the MUT is inferred by introducing (13) in (11). Another important aspect is the determination of the equivalent dielectric constant of the substrate.…”
Section: Sensitivity Enhancement 21 Planar Structures In Frequency-va...mentioning
confidence: 99%
See 2 more Smart Citations
“…For CSRR-based sensors, the ratio C /C that appears in (11) can be evaluated by isolating C and C from (7), however, the resulting expression is not as simple as (12). In this case, it is found that C /C is (13) and the dielectric constant of the MUT is inferred by introducing (13) in (11). Another important aspect is the determination of the equivalent dielectric constant of the substrate.…”
Section: Sensitivity Enhancement 21 Planar Structures In Frequency-va...mentioning
confidence: 99%
“…By measuring, or simulating, the response of the bare sensor, and the one of the sensor loaded with that MUT, ε r,eq , can be isolated from (12). If, in contrast, a CSRR is the sensing element, in this case, (13) and ( 11) must be used. The experimental validation of frequency-variation permittivity sensors based on different resonant elements, such as CSRRs, SRRs or DB-DGS resonators, has been reported in the literature [18,58].…”
Section: Sensitivity Enhancement 21 Planar Structures In Frequency-va...mentioning
confidence: 99%
See 1 more Smart Citation